A Note on Solvable Polynomial Algebras - Huishi Li (Computer Science Journal of Moldova, 2014)
In terms of their defining relations, solvable polynomial algebras introduced by Kandri-Rody and Weispfenning [J. Symbolic Comput., 9(1990)] are characterized by employing Gr\"obner bases of ideals in free algebras, thereby solvable polynomial algebras are completely determinable and constructible in a computational way.